PENGARUH PROGRAM STAND UP COMEDY SHOW DI METRO TV TERHADAP AKTUALISASI DIRI PENONTON (STUDI KASUS PENGARUH TAYANGAN STAND UP COMEDY SHOW DI METRO TV TERHADAP AKTUALISASI DIRI PENONTON DI CAFÃ© COFFEE TOFFEE, KALIMALANG) - Buana, Ayu Tirta; Asmara D.A, Yudha (Fakultas Komunikasi, Sastra, dan Bahasa, 2015)
This study was conducted to determine the effect of Program Stand up Comedy Show on Metro TV Audience Against Self-actualization (Case Study Effect of Impression Stand up Comedy Show on Metro TV Against Self Actualization Attendance at Café Coffee Toffee, Kalimalang). In this study, researchers used a hypodermic needle theory and the theory of Abraham Maslow's hierarchy of needs is self-actualization needs. This study uses a quantitative approach, in which the results obtained in the form of data. The population consists of 50 people, with a sample of 25 people. The method used was purposive sampling the researcher. Not through a random sample techniques, in which each member of the population has a chance of being sampled, based on the characteristics that made the researcher. Research data collection techniques using primary data (obtained from the study site) and secondary data (literature study). Data were analyzed  using SPSS for windows 21. 00. The data is then through the stages of editing, coding and tabulation. The study was conducted in order to find the effect of the program stand up comedy show on Metro Tv audience to self-actualization. Results of this study indicate that there are significant between stand up comedy show program on Metro TV audience against self- actualization